Real-world efficacy and safety of pangenotypic direct-acting antivirals against hepatitis C virus infection in Taiwan - Kao-Chi Chang (Nature Portfolio, 2021)
Abstract Clinical trials showed pangenotypic direct-acting antivirals’ (DAAs) excellent efficacy and safety when treating hepatitis C virus (HCV). Two pangenotypic regimens were examined, glecaprevir/pibrentasvir (GLE/PIB) and sofosbuvir/velpatasvir (SOF/VEL), in a real-world Taiwanese setting, including all HCV patients treated with GLE/PIB or SOF/VEL from August 2018 to April 2020. The primary endpoint was sustained virologic response 12 weeks after treatment cessation (SVR12), including adverse events (AEs). A total of 1,356 HCV patients received pangenotypic DAA treatment during the study: 742 and 614 received GLE/PIB and SOF/VEL, respectively. The rates of SVR12 for GLE/PIB and SOF/VEL were 710/718 (98.9%) and 581/584 (99.5%), respectively, by per-protocol analysis, and 710/742 (95.7%) and 581/614 (94.6%), respectively, by evaluable population analysis. Eleven (GLE/PIB: 8, SOF/VEL: 3) did not achieve SVR12. The most common AEs for GLE/PIB and SOF/VEL were pruritus (17.4% vs. 2.9%), abdominal discomfort (5.8% vs. 4.4%), dizziness (4.2% vs. 2%), and malaise (3.1% vs. 2.9%). Laboratory abnormalities were uncommon; only < 1% exhibited elevated total bilirubin or aminotransferase levels with both regimens. Five drug discontinuations occurred due to AEs (bilirubin elevation: 3; dermatological issues: 2). Pangenotypic DAAs GLE/PIB and SOF/VEL are effective and well tolerated, achieving high SVR12 rates for patients with all HCV genotypes.